IMPROVING METHODOLOGICAL PREPARATION FOR DEVELOPING STUDENTS’ CORE COMPETENCIES IN ROBOTICS UNDER FORMATIVE ASSESSMENT CONDITIONS (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
This article examines the scientific and pedagogical foundations of improving methodological preparation for developing students’ core competencies in robotics through formative assessment strategies in secondary and specialized education. In the context of rapid technological transformation and the global integration of STEM education, robotics has emerged as a powerful platform for nurturing algorithmic thinking, engineering design skills, and creative problem-solving abilities in young learners. The study presents a conceptual framework that combines diagnostic feedback loops, iterative learning cycles, and project-based formative tasks to support students in mastering robotics competencies aligned with the demands of the Fourth Industrial Revolution. A mixed-methods research design involving pedagogical experiments, expert interviews, and quantitative analysis was applied to determine the effectiveness of formative assessment in robotics learning environments. The findings indicate significant improvements in learners’ technical proficiency, creative thinking, and collaboration skills when formative assessment practices are embedded in structured methodological preparation. The article concludes by outlining practical recommendations for integrating robotics and formative assessment in national education systems, particularly in developing countries, while aligning with international STEM and competency-based education standards.